546 Antegrade in-stent CTO recanalization. (8th December 2021) - Giovannini, Davide; Pesarini, Gabriele; Mammone, Concetta
Abstract: Methods and results: A 64-year-old man with prior PCI and stent of proximal LAD due to an anterior ST-elevation myocardial infarction (STEMI) presented with exertional angina (CCS III), despite optimal medical therapy (OMT). The echocardiogram showed a dilatated left ventricle with anterior and apical akinesia and a severely reduced left ventricle ejection fraction. Coronarography was performed and a chronic total occlusion was found at the proximal edge of the stent previously implanted in the proximal LAD, with a thin tapered entry (J-CTO score 1). Moderate angiographic disease was present in the circumflex (LCX) and in the right coronary artery (RCA). Interventional collaterals were absent. Dobutamine stress echocardiogram was performed to unmask myocardial viability. Indeed, during intravenous Dobutamine administration, we registered an increase in the left ventricle function, whereas only apex remained still akinetic. Accordingly, the patient underwent LAD CTO PCI using a 7 Fr EBU 4.0 guiding catheter, via right femoral artery access. The RCA ostium was engaged with a 6 Fr Judkins right 4.0 guiding catheter, via right radial artery access. Antegrade wire escalation technique was attempted. Due to scarce support, a 7 Fr Guidion guiding catheter extension and a Corsair microcatheter were placed in the proximal LAD. Antegrade crossing was very difficult due to intrastent high plaque burden. The occlusion was crossed with an Asahi Conquest Pro 9 guidewire. Subsequently, an Asahi Gaia third guidewire was advanced through the intrastent segment and then in the distal part of LAD. The advance of microcatheter was challenging but successfully achieved taking advantage of the low profile, high torqueability and trackability of the Asahi Corsair Pro microcatheter. Microcatheter tip injection confirmed the correct position in the vessel's true lumen. An Asahi Grand Slam guidewire was placed in the distal LAD to provide extra support for delivery of interventional devices. The lesion was pre-dilated with progressively larger balloon, starting from a 1.1 mm diameter semi-compliant over-the-wire balloon (OTW). Two stents were implanted with a minimal overlap at the distal edge of the proximal stent (Resolute Onyx 3.0 × 38 mm and 2.5 × 24 mm). The result was improved with stents high-pressure post-dilatation and with selective intracoronary adenosine and nitroglycerin administration with final Thrombolysis in Myocardial Infarction (TIMI) grade 3 flow. The total amount of contrast media used was 210 ml. The total procedure time was with 125 min with 45 min of fluoroscopy. No complications occurred. Conclusions: CTO PCI still represents one of the most challenging subsets of coronary interventions despite the improvement in technology and techniques. Although data regarding percutaneous PCI CTO are still inconsistent, successful CTO recanalization has been associated with relief of angina and ischemia-related dyspnoea (Werner at al., 2018). In stable patients CTO PCI has been associated with a lower risk of death, stroke, and coronary artery bypass grafting and less recurrent angina pectoris in some registry studies (Christakopoulos et al., 2015). Additionally, CTO PCI increased left ventricle function in a subgroup of patients with LAD CTO (Henriques et al., 2016). Conversely, randomized multicentre failed to demonstrate a superiority of CTO PCI medical to OMT in terms of major adverse cardiac events (MACE) and all-cause mortality.